The advancement of music in enlightenment England : Benjamin Cooke and the Academy of Ancient Music - Egginton, Tim (Music in Britain, 1600-2000., 2014)
Amidst the cosmopolitan, fashion-obsessed concert life of later eighteenth-century London there existed a discrete counterculture borne of native musical culture.